2018
DOI: 10.1177/000313481808400831
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telemedicine in Surgical Education: A Seven-Year Experience

Abstract: Uniformity in surgical education is challenging because surgical experience is based on rotation assignments. With work hour restrictions, the likelihood of residents being exposed to rare or unusual cases is diminished. Telemedicine may create a new learning paradigm for surgical education and supplement exposure for rare or unusual cases. A retrospective review (2010–2016) of teleconferences involving trauma centers worldwide was conducted. Participating hospitals included centers from underdeveloped countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This is intuitive specially for physicians who frequently use telemedicine, including those involved in internal medicine and family medicine [52]. Our findings are consistent with those of previous studies [53][54][55]. Ha et al reported that physicians who had a structured educational program in telemedicine had greater confidence in addressing clinical problems than those who did not receive an educational program [56].…”
Section: Principal Findingssupporting
confidence: 91%
“…This is intuitive specially for physicians who frequently use telemedicine, including those involved in internal medicine and family medicine [52]. Our findings are consistent with those of previous studies [53][54][55]. Ha et al reported that physicians who had a structured educational program in telemedicine had greater confidence in addressing clinical problems than those who did not receive an educational program [56].…”
Section: Principal Findingssupporting
confidence: 91%
“…Some are clearly intended to improve clinical care by providing consultant telehealth services [ 6 7 8 9 10 11 12 ]. Others create online learning modules for trainees or educate clinicians on advanced topics and rare cases [ 13 14 15 16 ]. Our intervention hybridized these goals — we hoped that detailed case discussions would provide an educational opportunity for clinicians working in Malawi, allowing them to make more appropriate management decisions that could result in improved patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…All of our group educational activities were converted to videoconferencing. 8 , 9 Weekly grand rounds, morbidity and mortality conference, guest speakers, and journal club were held during the daytime. Core Curriculum and board exam preparation continued but were moved to evening and recorded, due to the demands of ongoing clinical duties.…”
mentioning
confidence: 99%